Аж богдын нурууны физик газарзүйн тодорхойлолт - Э, Авирмэд; Б, Баянжаргал (Proceedings of the Mongolian Academy of Sciences, 2017)
Mountain Aj Bogd is one of branch mountains the mount systems Mongol Altai, which is located at the middle part of Mongol Altai mountain. Mountain Aj Bogd is similar with surface typology, deposits, form relief, erosion and accumulation process, mountain side, dissection, age and landscape of main mountains of Mongol Altai. Aj Bogd Mountain is a mounting system had existed which surrounding by valleys and depressions and related by kotal and pass from the main ridge of the Mongolian Altai mountains. The Aj Bogd Mountain segregated to the east by Gobi Khonin Us, to the north from the mountain Khubch by pass Zoolin Bogd and the Mongol Altai mountain by depressions of Alag lake, to the west from mountains Ikh Tayan by dale of the Tuhum,Tooroi, to the south by Nomingiin gobi. The highest peak of this mountain Aj Bogd is 3093.3 m high above the sea level. The relief and peak of a mountain is mostly cupola or plane shaped because of in longest time weathered by wind and water.